Production Ethics in An Islamic Economic Perspective - Muhammad Nurdin Jamil; Sirajuddin; Muhammad Hamsah; Nurchamidah; Rina Rosia (al-Afkar, Journal For Islamic Studies, 2024)
This research is a qualitative research that aims to analyze the Islamic concept of production ethics in an Islamic economic system to improve human welfare and benefit. Production is the initial activity in producing goods that will be consumed by the general public. Production in Islamic economics is a form of activity carried out to realize benefits or add to it by exploring the economic resources provided by Allah SWT, so that it becomes a benefit, to meet human needs. Production ethics can be interpreted as the basic capital of one's morality in carrying out production activities related to behavior in producing goods and services in economic activities. The principle of conventional production activities emphasizes efficiency optimization and profit optimization. While the principle of production activities in Islam is concerned with the benefit of the people, not only profit-oriented. Ethics in production activities with an Islamic economic perspective, the first is choosing halal goods, namely ayyibāt. Second, the protection of natural wealth, should be done without damaging the environment (nature). Third, the guarantee of goods and services that will be produced, does not produce goods and services that are contrary to maqāṣid al-syarī'ah.